The Role of Anti-Corruption Education in Supporting a Bright Future for the Nation - Maharani, Yesy; Mawaddah, Annisa; Amalia Kusfebriana, Riszka; Intan Kumala Sari, Siti; Hudi, Ilham (Journal of Asian Primary Education (JoAPE), 2024)
This article discusses how anti-corruption education serves as a proactive step in fostering a society that is aware of and responsive to corruption issues. By embedding anti-corruption principles into formal and informal education programs, the aim is to cultivate critical awareness and strong ethical standards among students. The method used is a Systematic Literature Review (SLR), collecting 36 articles from Google Scholar published between 2020 and 2024. This article aims to provide valuable perspectives for educators, policymakers, and the broader community on the importance of anti-corruption education in driving positive social transformation.